ACADEMIC PROCRASTINATION OF STUDENTS - Dyla Fajhriani N (Abjadia, 2020)
The process of college education differs from educational institutions in secondary schools or primary schools because the subject matter given to students is broader than the subject matter provided at secondary schools or elementary schools. students must also learn to prepare themselves not only to do their work but also in facing exams. Students often procrastinate on assignments given by lecturers for a period of a week. Most students will do their work when the allotted time is getting closer. The actual tasks can be completed faster than the deadline   it is not done immediately because they feel that if done faster or with the Overnight Speeding System "SKS" will not affect the results of the assessment. Lecturers will not give rewards for tasks that are completed faster. So that other activities or jobs that are less important (watching television or cinema, hanging out, playing games with peers) actually take precedence because it gives more self satisfaction.  This study aims to determine the academic procrastination of students in doing assignments. The research used is quantitative research using survey methods of 40 students. The results of research conducted by researchers found that the level of academic procrastination of Islamic Guidance Counseling Department students is low.